MOLECULAR DETECTION AND CHARACTERIZATION OF THE fbpA GENE IN MULTI DRUG RESISTANT (MDR) Mycobacterium tuberculosis ISOLATES FROM MAKASSAR - Widyastuti, Helmy; Agus, Rosana; Wahyudi, Dedeng (Jambura Journal of Health Sciences and Research, 2025)
Antibiotics have been widely used to treat tuberculosis (TB), yet the emergence of drug-resistant strains remains a serious global concern, highlighting the need for new molecular biomarkers to assess treatment success more accurately. Mycobacterium tuberculosis adheres to host tissues through the fbpA gene, which plays a vital role in bacterial virulence and persistence. The novelty of this study lies in exploring the fbpA gene as a potential biomarker for evaluating TB treatment response, differing from previous research that mainly targets drug-resistance genes such as rpoB, katG, or inhA. This study offers a new perspective by focusing on a virulence-related gene that may reflect bacterial survival and therapy outcomes, particularly in Indonesian clinical samples where such data remain scarce. The study aimed to assess the potential of the fbpA gene as a treatment biomarker by detecting a 900 bp fragment using molecular techniques. Ten sputum samples were collected from the Tuberculosis Unit of HUM-RC, Hasanuddin University Hospital, Makassar, and underwent sputum decontamination, Ziehl-Neelsen staining, acid-fast bacilli examination, DNA isolation, PCR amplification, and gel electrophoresis. The results showed the presence of DNA bands in all samples, with variations in thickness and intensity corresponding to DNA concentration. These findings suggest that the fbpA gene could serve as a rapid and reliable molecular biomarker for monitoring bacterial load and evaluating treatment efficacy, supporting the development of more precise diagnostic tools for multidrug-resistant TB management.